2021
DOI: 10.1002/acm2.13386
|View full text |Cite
|
Sign up to set email alerts
|

Planning and delivery of intensity modulated bolus electron conformal therapy

Abstract: Purpose Bolus electron conformal therapy (BECT) is a clinically useful, well‐documented, and available technology. The addition of intensity modulation (IM) to BECT reduces volumes of high dose and dose spread in the planning target volume (PTV). This paper demonstrates new techniques for a process that should be suitable for planning and delivering IM‐BECT using passive radiotherapy intensity modulation for electrons (PRIME) devices. Methods The IM‐BECT planning and delivery process is an addition to the BECT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(43 citation statements)
references
References 26 publications
(70 reference statements)
1
34
0
Order By: Relevance
“…An alternative approach is the use of passive modulators, 15,16 which can achieve superior dose distributions with respect to bolus electron conformal therapy. 17 In principle, one could therefore use existing equipment to deliver electron treatments on shallow targets with a conformal dose distribution achieving FLASH regime. The landscape may change in the future with higher energy electrons (often referred to as very high-energy electrons [VHEEs]) delivered with beam scanning.…”
Section: Electronsmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative approach is the use of passive modulators, 15,16 which can achieve superior dose distributions with respect to bolus electron conformal therapy. 17 In principle, one could therefore use existing equipment to deliver electron treatments on shallow targets with a conformal dose distribution achieving FLASH regime. The landscape may change in the future with higher energy electrons (often referred to as very high-energy electrons [VHEEs]) delivered with beam scanning.…”
Section: Electronsmentioning
confidence: 99%
“…Such systems are, however, not routinely available in clinical practice. An alternative approach is the use of passive modulators, 15,16 which can achieve superior dose distributions with respect to bolus electron conformal therapy 17 . In principle, one could therefore use existing equipment to deliver electron treatments on shallow targets with a conformal dose distribution achieving FLASH regime.…”
Section: Beam Production and Deliverymentioning
confidence: 99%
“…As the HEE delivery machines currently deliver beam pulses every few milliseconds, and the pulses are typically on the order of one or more Gray-per-pulse, this would require a very fast moving MLC to achieve the desired field modulation and such a technology is not currently yet available [36]. Alternatively, there has been development of intensity modulated passive scattering applicator devices to achieve conformal and homogeneous dose, without compromising substantially maximum depths that can be treated [37,38]. Rahman et al [39] demonstrated the feasibility of plan and dose calculation with the use of this passive delivery method for an electron UHDR beam produced from a modified medical linac.…”
Section: Uhdr Hee Delivery Techniques and Challengesmentioning
confidence: 99%
“…BECT has the benefit of providing adequate dose coverage to the PTV, while reducing dose to distal critical structures and normal tissues and ensuring low whole‐body dose. BECT has been shown useful for treatment of post‐mastectomy chest wall 3 , 4 , 5 , 6 , 7 ; shallow sarcomas 3 , 4 , 8 ; ear, temple, 9 parotid, and buccal mucosa 4 , 10 ; nose 11 ; eye canthi 12 , 13 ; and extremities. 8 Currently, BECT is commercially available from two companies (.decimal, LLC, Sanford, FL and Adaptiiv Medical Technologies, Inc., Halifax, NS, Canada) that provide software based on bolus design algorithms, 8 , 14 integrate that software with the customer's treatment planning system, and allow for bolus fabrication through either milling of machinable wax 14 , 15 or 3D printing.…”
Section: Introductionmentioning
confidence: 99%
“…They are oriented to align with the divergence of the beam such that their axes project back to the nominal source position (100 cm upstream of isocenter). 9 , 17 , 19 , 20 Incident electrons are absorbed by the island blocks so that the underlying fluence in the patient is reduced locally by approximately the fraction of the cross‐sectional area of the field covered by the overlying nearby island blocks. This is possible because lateral scattering of the electrons, primarily due to air upstream of the intensity modulator and the machinable foam slab in which it is embedded, restores locally the downstream fluence uniformity, but to a reduced value.…”
Section: Introductionmentioning
confidence: 99%